2017
DOI: 10.1111/jfd.12672
|View full text |Cite
|
Sign up to set email alerts
|

Production‐level risk factors for syncytial hepatitis in farmed tilapia (Oreochromis niloticus L)

Abstract: Syncytial hepatitis (SHT) is an emerging viral disease of tilapia characterized by significant morbidity and mortality. This study aimed to establish the production-level shows that some production factors increase the risk incidence and severity of SHTon a farm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Moreover, farm size was a main contributor in transmission of infectious diseases among hydrodynamically linked farmed ponds, indicating that increments of separation distance between farmed ponds significantly prevent pathogen transmission (Salama & Murray, ). Kabuusu, Aire, Stroup, and Ferguson () also suggested that controlling number of pond production cycles per year and elevating weight of fish at time of transfer during culture seasons could also be practical approaches for aquaculture management. Taken together, to rigorously reinforce TiLV containment, control of fish density by employing the developed model framework can be accompanied with other administrative strategies of managing farm size and production cycles, and limiting cocultivation in tilapia farms in different geographic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, farm size was a main contributor in transmission of infectious diseases among hydrodynamically linked farmed ponds, indicating that increments of separation distance between farmed ponds significantly prevent pathogen transmission (Salama & Murray, ). Kabuusu, Aire, Stroup, and Ferguson () also suggested that controlling number of pond production cycles per year and elevating weight of fish at time of transfer during culture seasons could also be practical approaches for aquaculture management. Taken together, to rigorously reinforce TiLV containment, control of fish density by employing the developed model framework can be accompanied with other administrative strategies of managing farm size and production cycles, and limiting cocultivation in tilapia farms in different geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most prominent food-producing industries, contain- that increments of separation distance between farmed ponds significantly prevent pathogen transmission (Salama & Murray, 2011). Kabuusu, Aire, Stroup, and Ferguson (2018) also suggested that con-…”
Section: Aquaculture Management Strategiesmentioning
confidence: 99%
“…A study of production‐level risk factors for the presence and severity of SHT in Ecuador assessed tilapia strain, stocking density, fry weight at transfer, weather pattern, water temperature, dissolved oxygen, the number of days spent preparing the pregrow‐out pond, month of transfer to pregrow‐out pond, daily feeding rate, number of pond production cycles per year, year of stocking and mortality rate per production cycle (Kabuusu et al . ). It was found that infected populations showed about five times higher mortality levels than uninfected populations (RR = 4.8, 95% CI 2.9–7.9), with tilapia of the Chitralada strain showing twice as high mortality as GMT and GIFT strains (RR = 2.1, 95% CI 1.8–2.4) (Kabuusu et al .…”
Section: Epidemiologymentioning
confidence: 97%
“…It was found that infected populations showed about five times higher mortality levels than uninfected populations (RR = 4.8, 95% CI 2.9–7.9), with tilapia of the Chitralada strain showing twice as high mortality as GMT and GIFT strains (RR = 2.1, 95% CI 1.8–2.4) (Kabuusu et al . ). Excess mortality was significantly associated with dissolved oxygen, stocking density (fish/m2), number of pond production cycles per year (Kabuusu et al .…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation